ARTIKEL PLAGIARISM DALAM PENULISAN PROPOSAL SKRIPSI: STUDI KASUS PADA MAHASISWA SEMESTER VIII, PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS, UNIVERSITAS NUSA CENDANA - Elisna Huan (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2019)
The purpose of this study was to identify the forms of plagiarism committed by students of English Education, the Teaching and Education Faculty, the Teaching and Education Faculty, Nusa Cendana University when making a Thesis Proposal. By using this type of Descriptive Qualitative research, the author makes 10 Thesis Proposals for VIII Semester semester 2019 students as research samples. The author also uses an online software called SMALLSEOTOOLS to make it easier to identify student plagiarism. The research found various types of plagiarism actions such as Copy and paste, Translation, Covered plagiarism, Shake and paste collections, Clause quilts, Pawn sacrifice, Cut and slide, and Other dimensions. In addition, there were also 2 factors that formed the background of the act of plagiarism, namely internal factors, and external factors. Internal factors come from the students themselves, while internal factors come from outside the students.